The mediating effect of clinical belongingness on the relationship between anxiety and professional identity in nursing interns: a cross-sectional study - Zhang, Junhao; Wang, Lijia; Yang, Xue; Yang, Yuwei; Wu, Xuehua; Huang, Huaping; Li, Guirong (Frontiers in Medicine, 2025)
BackgroundPrevious studies have reported that anxiety negatively affects professional identity (PI), and clinical belongingness is positively correlated with PI among nursing interns. However, little is known about the relationship between anxiety, PI, and clinical belongingness among nursing interns.ObjectiveTo explore the relationship between PI, clinical belongingness, and anxiety among nursing interns, and to demonstrate the mediating role of clinical belongingness in this relationship.MethodsA cross-sectional study using an online questionnaire was conducted between November 2023 and January 2024 among 1,050 nursing interns from 26 teaching hospitals in Sichuan Province, China. A general information questionnaire, the Belongingness Scale-Clinical Placement Experience (BES-CPE), the Self-Rated Anxiety Scale (SAS), and the Professional Identity Questionnaire for Nursing Students (PIQNS) were used to collect data. SPSS (version 25.0) and AMOS (version 28.0) were used to analyze the data.ResultsNursing interns had moderate mean scores for all variables; PI (60.77 ± 12.18), clinical belongingness (115.99 ± 17.02), and anxiety (47.44 ± 8.75). Correlation analyses revealed that both PI (r = −0.129, p < 0.01) and clinical belongingness (r = −0.087, p < 0.01) were negatively correlated with anxiety and clinical belongingness was positively correlated with PI (r = 0.601, p < 0.01). The clinical belongingness of nursing interns had a mediating effect on the relationship between anxiety and PI (β = −0.072, 95% confidence interval = −0.133 to −0.013, p < 0.001), accounting for 40% of the total effect.ConclusionThe anxiety level of nursing interns can have a direct impact on the prediction of PI and an indirect influence on PI mediated by clinical belongingness. Accordingly, nursing educators and managers should screen and channel the mental health problems of nursing interns in a timely manner, improving their clinical belonging, which will help improve PI and ultimately improve the stability of the nursing workforce.